Feasibility of simultaneous integrated boost with forward intensity-modulated radiation therapy for multiple brain metastases - Ni, Lingqin; Liang, Xiaodong (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study: To evaluate the feasibility of whole-brain radiotherapy (WBRT) with a simultaneous integrated boost (SIB) by forward intensity-modulated radiation therapy (IMRT) in patients with 1–3 brain metastases. Material and methods : Two forward IMRT plans were implemented among 18 patients. In plan A, the prescribed dose was 30 Gy to the whole brain (PTV WNRT ) and 50 Gy to individual brain metastases (PTV boost ) delivered simultaneously in 10 fractions. In plan B, the prescribed dose was 30 Gy to the PTV WNRT and 40 Gy to the PTV boost . Plans were evaluated with regard to conformation number (CN), prescription isodose volume to target volume ratio (PITV), target coverage (TC), homogeneity index (HI), and the volume receiving at least 95% of the prescribed dose (V95). Plan A was implemented for 5 of these patients, and plan B was used for the remaining patients. Results : The mean values of CN, PITV, TC, and HI for the PTV boost were 0.71, 1.32, 0.97, and 0.07, respectively, for plan A and 0.65, 1.47, 0.97, and 0.05, respectively, for plan B. The mean values of TC, HI, and V95 for the PTV WNRT were 0.98, 0.45, and 99.71%, respectively, for plan A and 0.97, 0.27, and 99.61%, respectively, for plan B. All patients completed the planned radiotherapy (RT) schedule with no acute and late RT-related toxicity greater than grade 2. Conclusions : It is feasible to deliver WBRT with a SIB via forward IMRT for patients with 1–3 brain metastases with good dose conformity and acceptable toxicity.